Analisis Fungsi, Kategori, dan Peran Sintaksis Sebagai Kalimat Efektif dalam Teks Cerita Anak “Berbeda Itu Tak Apa” Buku Ajar Bahasa Indonesia Siswa Kelas I SD Negeri 050611 Aman Damai - Nurul Arfika; Ade Hermansyah Pohan; Elly Prihasti Wuriyani; Wisman Hadi (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
Children's story texts are events based on the time sequence experienced or in the form of imagination that tells the world of children. This story text is able to improve children's language skills through reading. The children's story text entitled "It's OK to be different" has an interesting story to research, namely effective sentences that will be analyzed using function, role and syntactic categories. This research aims to classify words in first grade Indonesian language textbooks at independent curriculum elementary schools. This research analysis uses qualitative descriptive methods. The technique used to collect data in this research is reading and note-taking, or listening. The results of this research can be found roles, functions and syntactic categories in first grade Indonesian language textbooks at independent curriculum elementary schools. This research is useful for helping students in the process of analyzing syntactic structures.